2005
DOI: 10.1038/ni1187
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional topology of self peptide–major histocompatibility complex binding by a human autoimmune T cell receptor

Abstract: Autoimmune diseases are caused by self-reactive lymphocytes that have escaped deletion. Here we have determined the structure of the trimolecular complex for a T cell receptor (TCR) from a patient with multiple sclerosis that causes autoimmunity in transgenic mice. The structure showed a TCR topology notably different from that of antimicrobial TCRs. Rather than being centered on the peptide-major histocompatibility complex, this TCR contacted only the N-terminal peptide segment and made asymmetrical interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
284
3
17

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(312 citation statements)
references
References 50 publications
8
284
3
17
Order By: Relevance
“…30 These hydrophobic residues may act as TCR contact points, implying a rather restricted set of TCR-complementary determinant region recognition elements, as well as a non-canonical orientation for the TCRs, as described in multiple sclerosis. 47,48 By contrast, the two HLA-DQ6-restricted 13-mer epitopes in the insulin B chain have several hydrophilic residues, rendering these peptides less likely to act as contact points of hydrophobic complementary determinant regions on pathogenic TCRs.…”
Section: Discussionmentioning
confidence: 99%
“…30 These hydrophobic residues may act as TCR contact points, implying a rather restricted set of TCR-complementary determinant region recognition elements, as well as a non-canonical orientation for the TCRs, as described in multiple sclerosis. 47,48 By contrast, the two HLA-DQ6-restricted 13-mer epitopes in the insulin B chain have several hydrophilic residues, rendering these peptides less likely to act as contact points of hydrophobic complementary determinant regions on pathogenic TCRs.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the ability of AEP-inhibited B cells to activate a MBPreactive T cell clone isolated from the periphery of a patient with MS (24). This MBP-restricted clone binds in an unconventional manner to the N-terminal segment of the 85-99 peptide and is unresponsive to HPLC-purified MBP in the absence of intracellular processing (41,42). We found that inactivation of AEP did not result in significant disruption of MBP peptide 85-99 presentation by these cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, this could also disturb the balance of positive selection and Treg generation. Of considerable interest is the notion that several class II MHC-presented epitopes that are recognized by disease causing T-cell clones are presented in an MHC binding register that is unusual because it minimizes binding to class II MHC molecules that themselves present genetic factors contributing to disease [49,50]. This holds true for epitopes recognized by T cells causing experimental allergic encephalomyelitis (EAE), or multiple sclerosis (MS), as well as epitopes recognized by type 1 diabetes causing T-cell clones specific for insulin [51].…”
Section: How Could Recessive Central Tolerance Fail?mentioning
confidence: 99%